Insufficient impact of the aldose reductase inhibitor cemtirestat on the skeletal system in type 2 diabetic rat model - Monika Martiniakova; Marta Soltesova Prnova; Veronika Kovacova; Vladimira Mondockova; Karol Svik; Piotr Londzin; Joanna Folwarczna; Radoslav Omelka (PLoS ONE, 2025)
Cemtirestat, a multi-target drug combining aldose reductase inhibition with antioxidant properties, is considered a promising therapeutic agent for chronic diabetic complications. Current evidence suggests that long-standing diabetes adversely affects skeletal health, leading to diabetic bone disease. As the impact of cemtirestat on the skeletal system in an animal model of type 2 diabetes mellitus (T2DM) is still unknown, our study first investigated its effect on impaired bone health in Zucker diabetic fatty (ZDF) rats. Adult rats were divided into four groups: L (untreated lean ZDF rats), D (untreated obese ZDF rats), DT2.5 (obese ZDF rats treated with 2.5 mg/kg/day cemtirestat), and DT7.5 (obese ZDF rats treated with 7.5 mg/kg/day cemtirestat), with cemtirestat treatment lasting 2 months. Group D had increased levels of plasma glucose, insulin, triglycerides, glycated hemoglobin, total cholesterol, alkaline phosphatase, alanine aminotransferase, C-terminal telopeptide of type 1 collagen, greater body weight, femoral weight, structure model index, reduced cortical bone volume fraction, cortical bone thickness, trabecular bone volume fraction, and trabecular thickness compared to group L. Cemtirestat supplementation only elevated plasma phosphate levels in group DT2.5, trabecular bone volume fraction and trabecular thickness in group DT7.5, but the treatment had no effect on other parameters demonstrated in ZDF rats by macroscopic analysis, micro-CT cortical bone analysis, and mechanical testing. These findings indicate that the efficacy of cemtirestat in restoring deteriorated bone health caused by T2DM is not substantiated due to its insufficient effect on the skeletal system in the ZDF rat model.